KEANEKARAGAMAN DAN DOMINANSI PLANKTON DI TAMBAK IKAN KAKAP PUTIH (Lates calcarifer) PT. SURI TANI PEMUKA (STP) SOBO, BANYUWANGI - Nuriyah, Sinta (JURNAL BIOSENSE, 2025)
This study aims to identify the diversity and dominance of plankton in white snapper (Lates calcarifer) ponds at PT. Suri Tani Pemuka, Banyuwangi, and to analyze the effect of water quality on the presence of plankton. The study was conducted from 13 to 26 December 2024, with sampling in two pond plots, namely Plot 26 A and Plot 28 B. The results showed that in Plot 26 A there was a high dominance of Chlorella species in phytoplankton and Brachionus in zooplankton, which indicated less than optimal water quality and reduced diversity. In contrast, Plot 28 B showed better water quality, with more balanced plankton diversity and dominance of Euplotes in zooplankton. These findings confirm that the presence of diverse plankton is an indicator of good water quality, which supports ecosystem stability and aquatic productivity. This study is expected to provide insight into fish pond management and aquatic resource conservation.